3D printed continuous CF/PA6 composites: Effect of microscopic voids on mechanical performance - He, Qinghao; Wang, Hongjian; Fu, Kunkun; Ye, Lin (Composites science and technology, 2020)
The production of continuous carbon fibre composites using a fused deposition modelling (FDM) method has addressed the problem of low mechanical performance of raw- or short-fibre reinforced polymer parts fabricated by the same process, due to the excellent specific strength and stiffness of continuous fibres. However, one key issue of 3D printed polymers or fibre-reinforced polymers is the formation of microscopic voids between individual filaments and within the filaments during the FDM process. This study aims to quantify the adverse effects of voids on 3D printed continuous fibre-reinforced polymer composites. Optical microscopy and micro-CT are used to quantify the void content in continuous CF/PA6 composites fabricated on a 3D printing platform. As a benchmark, 3D printed CF/PA6 composites with the same printing configurations were further processed by compression moulding (CM) with thickness controlled to achieve the minimum void content. Apart from tensile and three-point bending tests in the longitudinal and transverse directions, the study also evaluated the Mode I interlaminar fracture toughness of CF/PA6 composites. By revealing the substantial adverse effects of the microscopic voids in 3D printed composites, this study articulates the critical importance of developing in-process techniques during 3D printing to decrease the void content within the continuous fibre reinforced composites, for the sake of expanding practical applications of 3D printed continuous fibre composites.